Preparation process of artificially synthesized graphite coil material and graphite film

By repeatedly discharging and collecting the material to form the core and controlling the carbonization temperature and heating rate in the preparation of graphite heat dissipation film, the problem of interlayer adhesion damage is solved, and the yield and width of the finished graphite film are improved.

CN119191284APending Publication Date: 2024-12-27SHENZHEN STONEPLUS THERMAL MANAGEMENT TECHNOLOGIES LIMITED
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411262725.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing graphite heat dissipation film or graphite heat sink during carbonization, and the heat-raising of cracking is too fast, resulting in interlayer adhesion and hole damage, and the finished product yield is low.

Method used

By repeatedly discharging and retrieving, forming a polyimide roll core, controlling the gap between the rolls, carbonizing at a temperature increase rate of less than 2°C/min at a carbonization temperature range of 500 to 800°C, followed by graphitization and recombination The roll is controlled to control the unwinding tension of the calender and is treated with an intermediate frequency graphitization furnace and a vacuum carbonization furnace.

Benefits of technology

It effectively avoids interlayer adhesion and damage after carbonization, improves the width and yield of the finished product, and ensures the integrity and performance of the graphite film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191284A_ABST
    Figure CN119191284A_ABST
Patent Text Reader

Abstract

The invention provides a preparation process of an artificially synthesized graphite coil material. The preparation process comprises the following steps: preparing a polyimide strip; the method comprises the following steps: unwinding a polyimide strip through repeated unwinding-winding to form a polyimide winding core, controlling the unwinding linear speed to be greater than the winding linear speed so as to form a gap between winding layers in the polyimide winding core, and enabling the size of the gap to be 1.0-2.5 times of the thickness of the polyimide strip; vertically loading the polyimide roll core into an isostatic pressing graphite jig, and carbonizing in a carbonization furnace, wherein the highest carbonization temperature is 1000-1200 DEG C, and the temperature is increased at a heating rate of less than 2 DEG C / min in a carbonization temperature interval of 500-800 DEG C; and carbonizing the polyimide roll core, graphitizing, rewinding and calendering. The process can effectively solve the problems of interlayer adhesion damage, hole damage and low finished product yield when the graphite coil material is prepared from the artificial graphite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite materials, and in particular to a preparation process of artificial synthetic graphite coils and a graphite film. Background Art

[0002] With the advent of the 5G era, the power consumption of electronic products is 2 to 5 times that of 4G, and the heat generated will also increase several times compared to 4G, which is a great test for thermal interface materials and heat dissipation materials. In recent years, graphite heat dissipation, metal backplane, frame heat dissipation, thermal conductive gel heat dissipation, heat pipe heat dissipation, and heat spreader heat dissipation have appeared, among which graphite heat dissipation is the most widely used.

[0003] Compared with the heat dissipation of metal materials, graphite heat dissipation film or graphite heat sink has the following advantages: (1) high strength, and good toughness and flexibility; (2) good thermal conductivity, with the maximum in-plane thermal conductivity reaching 1900W / Mk, and thermal resistance 40% lower than aluminum and 20% lower than copper; (3) ultra-light, 30% lighter than aluminum of the same size and 80% lighter than copper; (4) excellent reprocessability, can be compounded with other film materials such as PET according to the application, can be cut and punched into schematic shapes, and can be bent multiple times.

[0004] At present, graphite heat dissipation film or graphite heat sink is usually made of artificial graphite. For example, the polyimide is divided into strips and rolled into a core, which is then loaded on a jig for carbonization, graphitization, rewinding and calendering. For large-width polyimide with a width of 300 to 650 mm, during the carbonization molding process, the vertically rolled polyimide raw material softens at high temperature. During the cracking process, the large-width polyimide quickly softens and accumulates due to the rapid cracking temperature rise, which greatly destroys the interlayer gap and causes the interaction between the layers of the large-width polyimide. After carbonization, the carbonized film product layers are adhered and damaged, and the graphitization is irreversible, resulting in hole damage, so the finished product yield is extremely low.

[0005] Therefore, a new preparation process is urgently needed to solve the above problems. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to provide a process for preparing artificial synthetic graphite coils, which can effectively solve the problems of interlayer adhesion and damage, hole damage, and low finished product yield when preparing graphite coils from artificial graphite.

[0007] To achieve the above object, the first aspect of the present invention provides a process for preparing an artificial synthetic graphite coil, comprising:

[0008] (1) preparing a polyimide strip;

[0009] (2) the polyimide strip is unwound by repeatedly unwinding and rewinding to form a polyimide core, and the unwinding line speed is controlled to be greater than the rewinding line speed so that a gap is formed between the layers in the polyimide core, and the size of the gap is 1.0 to 2.5 times the thickness of the polyimide strip;

[0010] (3) vertically loading the polyimide core into an isostatic graphite jig and placing it into a carbonization furnace for carbonization, wherein the maximum carbonization temperature is 1000 to 1200° C. and the temperature is increased at a heating rate of less than 2° C. / min in a carbonization temperature range of 500 to 800° C.;

[0011] (4) The polyimide core is graphitized, rewound and calendered after carbonization.

[0012] In the technical solution adopted by the present invention, the roll is unwound by repeated unwinding and rewinding before carbonization, and the unwinding and rewinding speeds are controlled so that the size of the gap formed between the roll layers in the roll core is 1.0 to 2.5 times the thickness of the polyimide strip. This gap can make the carbonization process evenly heated, obtain a good carbonization effect, and the layers of polyimide are not easy to interact with each other, so as to avoid the adhesion and damage between the layers of the carbonized film product after carbonization. The inventor found that the carbonization cracking weight loss of polyimide at 500 to 800°C is more concentrated, and the carbon residue ratio and mass loss ratio in this temperature range are in the highest range. In this temperature range, slowing down the heating rate and heating at a heating rate of less than 2°C / min can make the polyimide film slowly undergo deoxidation, dehydrogenation, denitrogenation, heat absorption and weight loss cracking reactions in this temperature range, so that the cracking deformation is less, so the product is well formed.

[0013] As a technical solution of the present invention, the polyimide material is slit into strips to obtain the polyimide strips with a width of 630 mm.

[0014] As a technical solution of the present invention, the linear speed of the material discharge is 6 to 8 m / min, and the linear speed of the material collection is 5 to 7 m / min.

[0015] As a technical solution of the present invention, the carbonization is carried out in a vacuum carbonization furnace, and the vacuum degree is below 250mba.

[0016] As a technical solution of the present invention, the heating rate of the carbonization temperature in the range below 500°C is 3-7°C / min, and the heating rate of the carbonization temperature in the range from 800°C to the maximum carbonization temperature is 2-4°C / min.

[0017] As a technical solution of the present invention, the holding time at the highest carbonization temperature is 15 to 40 minutes.

[0018] As a technical solution of the present invention, graphitization is performed in a medium frequency graphitization furnace, and the furnace is evacuated and then argon gas is introduced for replacement to maintain a slight positive pressure in the furnace.

[0019] As a technical solution of the present invention, the maximum graphitization temperature is 2500-3200°C, and the heating rate of the graphitization temperature in the range below 1000°C is 5-10°C / min, the heating rate of the graphitization temperature in the range from 1000°C to the maximum graphitization temperature is 0.1-3.0°C / min, and the insulation time at the maximum graphitization temperature is 20-40min.

[0020] As a technical solution of the present invention, the effective width of the calender used for the calendering is 650 mm, and the unwinding tension during the calendering is controlled to be 2.5 to 10.0 N·m.

[0021] The second aspect of the present invention provides a graphite film, which is made by the aforementioned preparation process of synthetic graphite coils and has a width of 500-650 mm. The graphite film has not only a large width, but also a high finished product yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a graph showing the changes in carbon residue ratio and carbonization temperature during the carbonization process of polyimide.

[0023] Figure 2 This is a partial surface view of the artificial synthetic graphite coil of Example 1.

[0024] Figure 3 This is a partial surface view of the artificial synthetic graphite coil of Comparative Example 1.

[0025] Figure 4 This is a partial surface view of the artificial synthetic graphite coil of Comparative Example 2. DETAILED DESCRIPTION

[0026] The invention provides a preparation process of an artificial synthetic graphite coil, comprising the following steps.

[0027] (1) Prepare a polyimide strip.

[0028] (2) The polyimide strip is unwound by repeatedly unwinding and rewinding the strip to form a polyimide roll core.

[0029] (3) The polyimide core is vertically loaded into an isostatically pressed graphite jig and placed into a carbonization furnace for carbonization.

[0030] (4) The polyimide core is graphitized, rewound and calendered after carbonization.

[0031] In step (1), the polyimide material is stripped to obtain a polyimide strip with a width of 630 mm. Of course, the width of the polyimide strip can also be other sizes, and its width needs to be larger than the target mass-produced artificial graphite coil. For example, a polyimide strip with a width of 630 mm can be used to produce an artificial graphite coil with a width of 550 mm. The width of the target mass-produced graphite film obtained by this preparation process is 500-650 mm.

[0032] In step (2), the line speed of unwinding is controlled to be greater than the line speed of collecting so that a gap is formed between the layers in the polyimide core, and the size of the gap is 1 to 2.5 times the thickness of the polyimide strip. As an example, the size of the gap can be, but not limited to, 1.0 times, 1.2 times, 1.5 times, 1.7 times, 2.0 times, 2.2 times, 2.4 times, and 2.5 times the thickness of the polyimide strip. The thickness of the polyimide strip can be 30 μm to 100 μm. As an example, the thickness of the polyimide strip can be, but not limited to, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, and 100 μm. The gap formed between the layers in the polyimide core should not be too small, otherwise it will cause uneven heating of the inner graphite layer and affect the carbonization effect. Of course, the gap should not be too large, otherwise the volume of the core will increase. Due to the volume of the carbonization furnace, the amount of carbonization in the furnace will be reduced, affecting the carbonization efficiency. The line speed of unloading is 6 to 8 m / min. As an example, the line speed of unloading can be but not limited to 6 m / min, 7 m / min, and 8 m / min. The line speed of collecting is 5 to 7 m / min. As an example, the line speed of unloading can be but not limited to 5 m / min, 6 m / min, and 7 m / min. The gap size between the layers can be controlled by repeatedly unloading and collecting and controlling the speed of unloading and collecting to achieve uniform heating during carbonization.

[0033] In step (3), the inventors studied the changes in the carbon residue ratio and carbonization temperature of polyimide during the carbonization process, and the results are as follows: Figure 1 As shown. Figure 1The results show that the carbonization cracking reactions such as deoxidation, dehydrogenation, denitrification, endothermic and weight loss are mainly concentrated in 500-800°C. Heating the temperature at a heating rate of less than 2°C / min in the carbonization temperature range of 500-800°C can make the polyimide film slowly undergo deoxidation, dehydrogenation, denitrification, endothermic and weight loss cracking reactions in this temperature range, so that the cracking deformation is small, so the product is well formed. The heating rate in the carbonization temperature range of 500-800°C can be, but is not limited to, 0.2°C / min, 0.5°C / min, 0.7°C / min, 1.0°C / min, 1.2°C / min, 1.5°C / min, 1.7°C / min, and 2.0°C / min. After 1200°C, the carbon residue ratio remains basically unchanged, so the maximum carbonization temperature is 1000-1200°C. As an example, the maximum carbonization temperature can be, but not limited to, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C, 1100°C, 1120°C, 1140°C, 1160°C, 1180°C, 1200°C. The holding time at the maximum carbonization temperature is 15-40 minutes. As an example, the holding time can be, but not limited to, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes. Carbonization is carried out in a vacuum carbonization furnace, and the vacuum degree is below 250mba. The heating rate of the carbonization temperature in the range below 500°C is 3 to 7°C / min. As an example, the heating rate can be but not limited to 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min. The heating rate from room temperature to 500°C can be relatively large to accelerate the reaction rate. The heating rate of the carbonization temperature in the range from 800°C to the maximum carbonization temperature is 2 to 4°C / min. As an example, the heating rate can be but not limited to 2.0°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min, 3.0°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4°C / min. The heating rate in the range from 800°C to the maximum carbonization temperature should not be too fast to avoid the rapid heat affecting the cracking reaction of the polyimide.

[0034] In step (4), after carbonization is completed, the carbonized product is cooled to room temperature and graphitized in a medium frequency graphitization furnace. After the furnace is evacuated, argon gas is introduced for replacement to maintain a slightly positive pressure in the furnace. The maximum graphitization temperature is 2500-3200°C, and the insulation time at the maximum graphitization temperature is 20-40 minutes. As an example, the maximum graphitization temperature may be, but is not limited to, 2500°C, 2600°C, 2700°C, 2800°C, 2900°C, 3000°C, 3100°C, and 3200°C. The insulation time at the maximum graphitization temperature may be, but is not limited to, 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes, 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes, and 40 minutes. The heating rate in the graphitization temperature range below 1000°C is 5-10°C / min. As an example, the heating rate may be, but not limited to, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min. The heating rate in the graphitization temperature range from 1000°C to the maximum graphitization temperature is 0.1-3.0°C / min. As an example, the heating rate may be, but not limited to, 0.1°C / min, 0.5°C / min, 1.0°C / min, 1.5°C / min, 2.0°C / min, 2.5°C / min, and 3.0°C / min. The heating rate at high temperature should not be too fast to avoid rapid heating affecting the graphitization effect.

[0035] The effective width of the calender used for calendering is 650mm, and the unwinding tension during calendering is controlled to be 2.5-10.0N·m. As an example, the unwinding tension during calendering can be, but is not limited to, 2.5N·m, 3.0N·m, 3.5N·m, 4.0N·m, 4.5N·m, 5.0N·m, 5.5N·m, 6.0N·m, 6.5N·m, 7.0N·m, 7.5N·m, 8.0N·m, 8.5N·m, 9.0N·m, 9.5N·m, 10.0N·m. The unwinding tension during calendering is controlled to this numerical range, so that the finished graphite coil can be fully calendered and have good performance. Otherwise, if the unwinding tension is too large, the calendered finished graphite coil will shrink severely and affect the performance. If the unwinding tension is too small, the calendering effect will be affected, resulting in insufficient calendering. During calendering, the graphitized graphite coil and the release film can be calendered together to facilitate the subsequent use of the synthetic graphite coil.

[0036] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0037] Example 1

[0038] This embodiment is a process for preparing an artificial synthetic graphite coil, which is characterized by comprising the following steps.

[0039] (1) The polyimide material is slit to obtain polyimide strips with a width of 630 mm (thickness of 60 μm).

[0040] (2) The polyimide strip is unwound by repeated unwinding and rewinding to form a polyimide core, and the unwinding line speed is controlled to be 8 m / min, and the rewinding line speed is controlled to be 6 m / min, and a gap is formed between the layers in the polyimide core, and the size of the gap is 9 mm.

[0041] (3) The polyimide core is vertically loaded into an isostatic graphite jig and placed in a vacuum carbonization furnace for carbonization, and the vacuum degree is below 250 mba. The carbonization temperature is increased at a rate of 4°C / min from room temperature to 500°C, 1°C / min from 500°C to 800°C, and 3°C / min from 800°C to 1100°C. The holding time at 1100°C is 30 min.

[0042] (4) After the carbonization temperature drops to room temperature, the carbonized product is transferred to a medium frequency graphitization furnace for graphitization. The furnace is evacuated and then replaced with argon gas to maintain a slightly positive pressure in the furnace. The heating rate of the graphitization temperature from room temperature to 1000°C is 8°C / min, the heating rate from 1000°C to 3000°C is 1.5°C / min, and the holding time at 3000°C is 35 minutes. After graphitization, the product is rewound and calendered with a PET release film, and the unwinding tension during calendering is controlled to be 6.5N·m.

[0043] Through this preparation process of artificial synthetic graphite coil, artificial graphite coil with a width of 550mm can be produced, such as Figure 2 As shown, the surface is intact without any holes, creases or other damage. Using this preparation process, the finished product yield can reach 85%.

[0044] Example 2

[0045] This embodiment is a process for preparing an artificial synthetic graphite coil, which is characterized by comprising the following steps.

[0046] (1) The polyimide material is slit to obtain polyimide strips with a width of 630 mm (thickness of 60 mm).

[0047] (2) The polyimide strip is unwound by repeated unwinding and rewinding to form a polyimide core, and the unwinding line speed is controlled to be 8 m / min, and the rewinding line speed is controlled to be 5 m / min, and a gap is formed between the layers in the polyimide core, and the size of the gap is 12 mm.

[0048] (3) The polyimide core is vertically loaded into an isostatic graphite jig and placed in a vacuum carbonization furnace for carbonization, and the vacuum degree is below 250 mba. The carbonization temperature is increased at a rate of 6°C / min from room temperature to 500°C, the carbonization temperature range from 500°C to 800°C is increased at a rate of 0.5°C / min, the carbonization temperature range from 800°C to 1200°C is increased at a rate of 2°C / min, and the holding time at 1200°C is 25 min.

[0049] (4) After the carbonization temperature drops to room temperature, the carbonized product is transferred to a medium frequency graphitization furnace for graphitization. The furnace is evacuated and then argon is introduced for replacement to maintain a slight positive pressure in the furnace. The heating rate of the graphitization temperature from room temperature to 1000°C is 10°C / min, the heating rate from 1000°C to 3100°C is 2.5°C / min, and the holding time at 3100°C is 25min. After graphitization, the product is rewound and calendered with a PET release film, and the unwinding tension during calendering is controlled to be 8.5N·m.

[0050] The artificial graphite coil with a width of 549 mm can be obtained by the preparation process of the artificial synthetic graphite coil. The finished product yield can reach 96% by adopting the preparation process.

[0051] Comparative Example 1

[0052] This comparative example is a preparation process of an artificial synthetic graphite coil, which is characterized by comprising the following steps.

[0053] (1) The polyimide material is slit to obtain polyimide strips with a width of 630 mm (thickness of 60 mm).

[0054] (2) The polyimide strip is directly rolled into a polyimide core, and the layers of the core are tightly wound.

[0055] (3) The polyimide core is vertically loaded into an isostatic graphite jig and placed in a vacuum carbonization furnace for carbonization, and the vacuum degree is below 250 mba. The carbonization temperature is increased at a rate of 4°C / min from room temperature to 500°C, 1°C / min from 500°C to 800°C, and 3°C / min from 800°C to 1100°C. The holding time at 1100°C is 30 min.

[0056] (4) After the carbonization temperature drops to room temperature, the carbonized product is transferred to a medium frequency graphitization furnace for graphitization. The furnace is evacuated and then replaced with argon gas to maintain a slightly positive pressure in the furnace. The heating rate of the graphitization temperature from room temperature to 1000°C is 8°C / min, the heating rate from 1000°C to 3000°C is 1.5°C / min, and the holding time at 3000°C is 35 minutes. After graphitization, the product is rewound and calendered with a PET release film, and the unwinding tension during calendering is controlled to be 6.5N·m.

[0057] Through this preparation process of artificial synthetic graphite coil, artificial graphite coil with a width of 542mm can be obtained, such as Figure 3 As shown, there are holes and damage on its surface. Using this preparation process, the finished product yield can reach 46%.

[0058] Comparative Example 2

[0059] This comparative example is a preparation process of an artificial synthetic graphite coil, which is characterized by comprising the following steps.

[0060] (1) The polyimide material is slit to obtain polyimide strips with a width of 630 mm (thickness of 60 mm).

[0061] (2) The polyimide strip is unwound by repeatedly unwinding and rewinding to form a polyimide core, and the line speed of unwinding is controlled to be 8 m / min, and the line speed of rewinding is controlled to be 6 m / min, and a gap is formed between the layers in the polyimide core, and the size of the gap is 9 mm.

[0062] (3) The polyimide core was vertically loaded into an isostatic graphite jig and placed in a vacuum carbonization furnace for carbonization, and the vacuum degree was below 250 mba. The temperature was raised from room temperature to 1100°C at a rate of 3°C / min, and kept at 1100°C for 30 min.

[0063] (4) After the carbonization temperature drops to room temperature, the carbonized product is transferred to a medium frequency graphitization furnace for graphitization. The furnace is evacuated and then replaced with argon gas to maintain a slightly positive pressure in the furnace. The heating rate of the graphitization temperature from room temperature to 1000°C is 8°C / min, the heating rate from 1000°C to 3000°C is 1.5°C / min, and the holding time at 3000°C is 35 minutes. After graphitization, the product is rewound and calendered with a PET release film, and the unwinding tension during calendering is controlled to be 6.5N·m.

[0064] Through this preparation process of artificial synthetic graphite coil, artificial graphite coil with a width of 530mm can be produced, such as Figure 4 As shown, there are holes, creases and other damages on the surface. Using this preparation process, the yield of the finished product can reach 20%.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A process for preparing synthetic graphite coils, characterized in that: include: (1) preparing a polyimide strip; (2) the polyimide strip is unwound by repeatedly unwinding and rewinding to form a polyimide core, and the unwinding line speed is controlled to be greater than the rewinding line speed so that a gap is formed between the layers in the polyimide core, and the size of the gap is 1.0 to 2.5 times the thickness of the polyimide strip; (3) vertically loading the polyimide core into an isostatic graphite jig and placing it into a carbonization furnace for carbonization, wherein the maximum carbonization temperature is 1000 to 1200° C. and the temperature is increased at a heating rate of less than 2° C. / min in a carbonization temperature range of 500 to 800° C.; (4) The polyimide core is graphitized, rewound and calendered after carbonization.

2. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: The polyimide material is slit to obtain the polyimide strips with a width of 630 mm.

3. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: The linear speed of the material discharge is 6-8 m / min, and the linear speed of the material collection is 5-7 m / min.

4. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: The carbonization is carried out in a vacuum carbonization furnace, and the vacuum degree is below 250mba.

5. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: The heating rate in the range of carbonization temperature below 500° C. is 3-7° C. / min, and the heating rate in the range of carbonization temperature from 800° C. to the maximum carbonization temperature is 2-4° C. / min.

6. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: The holding time at the highest carbonization temperature is 15 to 40 minutes.

7. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: Graphitization is carried out in a medium frequency graphitization furnace, and the furnace is evacuated and then argon gas is introduced for replacement to maintain a slight positive pressure in the furnace.

8. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: The maximum graphitization temperature is 2500-3200°C, and the heating rate of the graphitization temperature in the interval below 1000°C is 5-10°C / min, the heating rate of the graphitization temperature in the interval from 1000°C to the maximum graphitization temperature is 0.1-3.0°C / min, and the insulation time at the maximum graphitization temperature is 20-40min.

9. The process for preparing the synthetic graphite coil according to claim 1, characterized in that: The effective width of the calender used for the calendering is 650 mm, and the unwinding tension during the calendering is controlled to be 2.5 to 10.0 N·m.

10. A graphite film, made by the process for preparing the synthetic graphite coil according to any one of claims 1 to 9, with a width of 500 to 650 mm.

Citation Information

Cited By

  • Method for enhancing cohesion of graphite by regulating foaming thickness

    CN121292427A